How Law Student Prepare Their Life to Survive? - Niravita, Aprila; Sumardiana, Benny; Wedhatami, Bayangsari; Salam, Syukron; Kamal, Ubaidillah; Laskarwati, Batari; Syariefudin, Iqbal (Faculty of Law, Universitas Negeri Semarang, 2020)
Character education is an important element in the effort to prepare superior Indonesian human resources, it is of particular concern to be applied especially among students, there is a need for character education because the attitudes and behavior of the people and people of Indonesia now tend to ignore the noble values ​​of Pancasila which are highly respected and should be rooted in everyday attitudes and behaviors, values ​​such as honesty, politeness, togetherness and religious, gradually eroded by foreign cultures that tend to be hedonistic, materialistic, and individualistic, so that the noble character values ​​are ignored in the future if students and young people are not equipped with character education. Law students have their own challenges, especially in the era of globalization. This paper analyzes and illustrates the character strengthening program for law student activists in Semarang State University through several programs, namely public speaking, strengthening student idealism, strengthening advocacy capacitation and human rights assistance and self-motivation. This research is a field research with the object of research as activists of law students who are members of student organizations. This research confirms that the programs for strengthening the character of students experience several obstacles, one of which is the model used and a relatively short time. However, character education for student activists helps students to survive in real life as part of community members.